LEARNING ISLAMIC RELIGIOUS EDUCATION BASED ON THE INDEPENDENT CURRICULUM AT BRIGJEND KATAMSO PRIVATE HIGH SCHOOL MEDAN - Siregar, Bahtiar; Abrianto, Danny; Syahrial, Abdi; Sitorus, Panca Abdi (Proceeding International Seminar of Islamic Studies, 2024)
Independent Curriculum is a new policy inaugurated by the Ministry of Education and Culture government on the basis of independence in learning. The main advantage of this curriculum is that students, teachers and school institutions have greater independence in managing their learning. Based on the results of pre-research observations that the researcher explored with one of the subjects, the implementation of the Merdeka Curriculum at Brigjend Katamso Medan Private High School reached Phase E which was applied to class 11 only. So that research will be able to focus on learning in class xi in accordance with the research focus that has been formulated. The aims of this research are: 1) To describe the implementation of independent curriculum-oriented learning in Islamic religious education subjects at Brigjend Katamso Private High School, Medan. 2) To explain the challenges in implementing independent curriculum-oriented learning in Islamic religious education subjects at Brigjend Katamso Private High School, Medan. Identifying these problems, researchers used a qualitative approach with case study research. The data analysis technique used is the Miles and Huberman model in the form of data including: 1) Data Reduction; 2) Data Display; Conclusion/Verification. Meanwhile, data collection techniques in this research used participant observation, documentation and free guided interviews. learning Islamic Religious Education in the Merdeka Curriculum. Meanwhile, the assessment carried out by Islamic Religious Education teachers only uses 2 assessment methods, namely diagnostic assessment and formative assessment. Because the implementation of the Merdeka Curriculum has not been completed for one year, summative assessments have not been carried out by Islamic Religious Education teachers. Apart from that, there needs to be a deep understanding of the stakeholders in it so that the implementation and implementation of the Merdeka Curriculum will be better and more mature and running. in accordance with the goals and desires to be achieved.